The E-internal audit iso 9001:2008 based on accreditation form assessment matrix in study program for effectiveness of monitoring accreditation - . Marzuki; Maria Shusanti Febrianti; Andala Rama Putra (University of Bandar Lampung (UBL), 2013)
Accreditation is one of the forms of external quality guarantee system; it is a process that used in authorized institution in giving formal recognition that an institution has an ability to do certain activity. On the preparation process there are many things have to be done by study program by using internal audit in periodic time. Internal audit is an independence activity, objectivity, and consultatively which is designed to increase the organization’s operation. This study will specifically focus on internal process audits in preparation for accreditation of Study Program of Information Engineering at Bandar Lampung University, through conducting monitoring directly that can be accessed by some units in a management system. The guidelines and standards for internal audit issued by one of several organizations ISO, the quality management system ISO 9001: 2008, one of the requirements must be fulfilled is conducting periodic internal audits. This standard is good when applied in the preparation for the accreditation process, and accreditation assessment matrix as a guide in conducting internal audits.